2015
DOI: 10.1103/physrevb.91.115101
|View full text |Cite
|
Sign up to set email alerts
|

X-ray spectroscopic study ofBaFeO3thin films: AnFe4+ferromagnetic insulator

Abstract: We investigated the electronic and magnetic properties of fully oxidized BaFeO3 thin films, which show ferromagnetic-insulating properties with cubic crystal structure, by hard x-ray photoemission spectroscopy (HAXPES), x-ray absorption spectroscopy (XAS) and soft x-ray magnetic circular dichroism (XMCD). We analyzed the results with configuration-interaction (CI) cluster-model calculations for Fe 4+ , which showed good agreement with the experimental results. We also studied SrFeO3 thin films, which have an F… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 49 publications
3
21
0
Order By: Relevance
“…As seen in Fig. 4, off the Bragg condition the measured intensity has features that resemble an x-ray absorption spectrum of these ferrates, as expected, where the strong prepeak feature between 527.0-529.5 eV arises from the oxygen ligand holes due to the negative charge transfer energy [31,40,41]. At the Bragg condition, there is a clear enhancement of the intensity within the prepeak region only.…”
Section: Film Results Discussionsupporting
confidence: 77%
“…As seen in Fig. 4, off the Bragg condition the measured intensity has features that resemble an x-ray absorption spectrum of these ferrates, as expected, where the strong prepeak feature between 527.0-529.5 eV arises from the oxygen ligand holes due to the negative charge transfer energy [31,40,41]. At the Bragg condition, there is a clear enhancement of the intensity within the prepeak region only.…”
Section: Film Results Discussionsupporting
confidence: 77%
“…3, we show the amplitude of the reflectivity change, which is a measure of the spectral weight transfer indicative of the insulator-to-metal transition, as a function of laser fluence. From the clear threshold behavior of this quantity we deduce that a sufficiently high density of excited carriers reduces electron-electron and electron-phonon interactions, which are the origins of the insulating properties in BaFeO 3 thin films [16,17].…”
mentioning
confidence: 99%
“…After the deposition, BaFeO 2.5 thin films were annealed at 200 • C under ozone atmosphere to obtain BaFeO 3 thin films [16]. The quality of the thin-film samples were confirmed by xray diffraction, Fe 2p x-ray absorption spectroscopy, and Fe 2p core-level hard x-ray photoemission spectroscopy measurements by comparing cluster-model calculations, which found that the formal valence of Fe was 4+ [16,17]. The experimental geometry is shown schematically in Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations